2004
DOI: 10.1001/archopht.122.7.997
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Epithelial Ingrowth After Laser In Situ KeratomileusisWith Mechanical Debridement and Flap Suturing

Abstract: To evaluate the efficacy and safety of mechanical debridement and suturing of the laser in situ keratomileusis (LASIK) flap in the treatment of clinically significant epithelial ingrowth after LASIK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 18 publications
(35 reference statements)
0
27
0
1
Order By: Relevance
“…Flap suturing is a suggested method to create a tight junction between the stromal bed and the flap and prevent the recurrence of ingrowth. 4 In the case described, however, the paracentral location of the flap precluded the placement of sutures, as it was thought that the induced astigmatism and potential scarring would be severe.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Flap suturing is a suggested method to create a tight junction between the stromal bed and the flap and prevent the recurrence of ingrowth. 4 In the case described, however, the paracentral location of the flap precluded the placement of sutures, as it was thought that the induced astigmatism and potential scarring would be severe.…”
Section: Discussionmentioning
confidence: 91%
“…[3][4][5] This condition occurs up to several-fold times more often after retreatment than after primary LASIK flap creation. 5,6 The recurrence rate after ingrowth removal has been as high as 44%.…”
Section: Discussionmentioning
confidence: 99%
“…A more improved version of this treatment is to lift the flap, remove the ingrowth mechanically, and then suture the flap (Rojas MC et al, 2004). Suturing would ensure that the fistula closes properly, preventing further progression of ingrowth cells into the flap interface to allow complete healing.…”
Section: Epithelial Ingrowthmentioning
confidence: 99%
“…One study showed that no regrowth occurred after scraping of ingrowth under the flap with sutures (Rojas MC et al, 2004). One problem with this technique is the induction of astigmatism (Narvaez et al, 2006).…”
Section: Epithelial Ingrowthmentioning
confidence: 99%
“…When necessary, the initial surgical treatment of epithelial growth is accomplished with the elevation of the flap, removal of epithelial cells from the posterior surface of the flap and the stromal bed with a knife or similar instrument, and replacement of the flap without sutures or adhesive tissues (29) . In case of recurrent episodes of epithelial growth, additional measurements are typically made, including suturing the flap (35) (Figure 3), fibrin glue (36) or yag laser treatment (37) .…”
Section: Epithelial Growthmentioning
confidence: 99%